Particle dynamics in sheared particulate suspensions. Issue 2 (23rd November 2018) - Strybulevych, Anatoliy; Norisuye, Tomohisa; Hasselfield, Matthew; Page, John H.
Abstract : Measurements of particle dynamics of neutrally buoyant suspensions of non‐Brownian glass beads in a Couette cell using dynamic sound scattering are reported. The dynamics were studied under steady shear flow across the entire gap between the stator and rotor for shear rates from 0.26 to 6.59 s −1 and particle concentrations from 20% to 50%, thereby enabling a comprehensive investigation of the dynamics to be carried out. The average particle velocity profile varies linearly with depth inside the cell for all shear rates and concentrations. The fluctuations in the particle velocities are large, indicating that the particles are not confined to streamlines but continue to fluctuate substantially during steady flow. Our data indicate that the fluctuations are anisotropic. The components of the velocity fluctuations (granular temperature) parallel to the flow and in the vertical direction are much larger than in the radial direction. The fluctuation anisotropy decreases as the concentration increases. © 2018 American Institute of Chemical Engineers AIChE J, 65: 840–849, 2019